2020
DOI: 10.26464/epp2020060
|View full text |Cite
|
Sign up to set email alerts
|

On the loss mechanisms of radiation belt electron dropouts during the 12 September 2014 geomagnetic storm

Abstract: The loss mechanisms of radiation belt dropout during the 12 September 2014 storm were investigated using satellite measurements q During the initial phase of the storm, magnetopause shadowing was the dominant loss mechanism, supported by energyindependent decay and butterfly pitch angle distributions (PADs) q The wave-particle interactions played an important role in >1 MeV electron loss during the main phase of the storm and produced 90-peaked PADs at L < 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…interactions inside and outside the plasmapause are quite different due to the sharp change in plasma density, the prediction of the plasmapause location becomes very important for magnetospheric research (e.g., Hua et al, 2020b;Khoo et al, 2018Khoo et al, , 2019Ni et al, 2015;Ma et al, 2020;Summers et al, 2008;Xiang et al, 2020;Zhang et al, 2018Zhang et al, , 2019.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…interactions inside and outside the plasmapause are quite different due to the sharp change in plasma density, the prediction of the plasmapause location becomes very important for magnetospheric research (e.g., Hua et al, 2020b;Khoo et al, 2018Khoo et al, , 2019Ni et al, 2015;Ma et al, 2020;Summers et al, 2008;Xiang et al, 2020;Zhang et al, 2018Zhang et al, , 2019.…”
Section: Accepted Articlementioning
confidence: 99%
“…The plasmasphere, which is full of cold and dense plasma (electrons ~ 1 eV with density ~ 10 2 -10 4 cm -3 ), plays an important role in modulating the fluxes of energetic particles in the Earth's ring current and radiation belts (e.g., Cao et al, 2017;Darrouzet et al, 2009;Fu et al, 2020;Gu et al, 2011Gu et al, , 2012Gu et al, , 2020Hua et al, 2019;Kozyra et al, 1995;Lemaire and Gringauz, 1998;Ni et al, 2013;Orr and Webb, 1975;Sandel et al, 2003;Takahashi and Anderson, 1992;Webb and Orr, 1975;Yi et al, 2021;Zhou et al, 2020). The plasmasphere strongly influences the plasma properties of the inner magnetosphere by wave-particle interactions (e.g., Fu et al, 2016;Gary et al, 1994;Hua et al, 2020a;Ni et al, 2014Ni et al, , 2017Thorne and Horne, 1992;Wilson et al, 1992;Xiang et al, 2018;Young et al, 1981), and contributes to assessing the low-latitude boundary layer and plasma sheet (e.g., Cao et al, 2016;Elphic et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During active times, both magnetopause shadowing followed by outward radial diffusion and atmospheric precipitations due to wave‐induced pitch angle diffusion play important roles in the loss of radiation belt electrons (e.g., Li et al., 1997; Ma et al., 2020; Morley et al., 2010; Tu et al., 2010; Turner et al., 2012; Xiang et al., 2016). The inward movement of the magnetopause due to strong solar wind dynamic pressure ( P dyn ) can substantially deplete electrons at high L shells where electrons find themselves on open drift shells, which is called magnetopause shadowing (e.g., Shprits, Thorne, Friedel et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that outer belt electrons can also exhibit dramatic losses (Morley et al, 2010; Ni BB et al, 2013; Su ZP et al, 2014, 2016; Katsavrias et al, 2015; Engebretson et al, 2018; Tu WC et al, 2019, Ma X et al, 2020) and accelerations (Su ZP et al, 2015) during non‐storm periods. Losses of MeV electrons can be attributed to either adiabatic processes (the Dst effect during enhancement of the ring current (Kim and Chan, 1997) or non‐adiabatic processes.…”
Section: Introductionmentioning
confidence: 99%